Pnictogen (As, Sb, Bi) Nanosheets for Electrochemical Applications Are Produced by Shear Exfoliation Using Kitchen Blenders - Gusmão, Rui; Sofer, Zdeněk; Bouša, Daniel; Pumera, Martin (Angewandte Chemie (International ed. in English), 2017)
Layered materials are of high importance because of their anisotropy and as a source of 2D materials. Whilst there is a plethora of multi-elemental 2D materials, the number mono-elemental 2D materials is rather limited. Herein, we demonstrate that aqueous shear exfoliation can be used to obtain As, Sb, and Bi exfoliated nanosheets. Morphological and chemical characterization of the exfoliated materials shows a decrease in thickness, sheet-to-nanosheet scale, and partial oxidation owing to a higher surface area. The electrochemical performance is tested in terms of inherent electrochemistry, electron transfer, and sensing applications as demonstrated with ascorbic acid. Potential energy-related applications are evaluated in the hydrogen evolution reaction (HER), oxygen evolution reaction (OER), and oxygen reduction reaction (ORR), with shear-exfoliated Sb having the best electrochemical performance overall. These findings will have a profound impact on the preparation and application of 2D mono-elemental materials.
Keywords: layered materials; shear force exfoliation; pnictogens; hydrogen evolution reaction; ascorbic acid